2015
DOI: 10.1063/1.4918764
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial exchange coupling in cubic Heusler Co2FeZ (Z = Al and Si)/tetragonal Mn3Ga bilayers

Abstract: We have fabricated bilayer films of tetragonal Heusler-like D022 Mn3Ga and cubic Heusler Co2FeZ (Z = Si and Al) on (100) single-crystalline MgO substrates and investigated their structural and interfacial exchange coupling. The coupling in the Mn3Ga/Co2FeAl bilayer was either ferromagnetic or antiferromagnetic, depending on annealing temperature, whereas only antiferromagnetic exchange coupling was observed in the Mn3Ga/Co2FeSi bilayers. The effects of annealing on the structure and coupling strength in the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…The absolute values of negative J ex are comparable to those evaluated in the FeCo/MnGa bilayers [9] and larger than those in Co 2 FeSi (Al)/MnGa [12].…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The absolute values of negative J ex are comparable to those evaluated in the FeCo/MnGa bilayers [9] and larger than those in Co 2 FeSi (Al)/MnGa [12].…”
Section: Resultssupporting
confidence: 71%
“…However, there are no reports on such bilayer and also magnetic coupling of CMS and MnGa, which is fundamentally important to obtain perpendicular magnetization of CMS. We recently reported that MnGa film with interlayers of B2-ordered Co 2 FeSi (Al) cubic Heusler alloys exhibits AF (ferromagnetic and AF) Jex [12]. Therefore, it is interesting to study MnGa film with a CMS interlayer.…”
Section: Introductionmentioning
confidence: 98%
“…To evaluate J ex , the thickness of the Heusler film was fixed at 20 nm. To estimate H + and H − , an P-MOKE measurement was employed, consistent with reported values estimated from VSM hysteresis in previous studies[33,34]. Although both method yield the same result, it is easier to estimate H + and H − from a P-MOKE hysteresis loop than a VSM hysteresis loop.…”
mentioning
confidence: 75%
“…The film com- Refs. [33,34] properties, an X-ray diffractometer with Cu K α radiation was used. To examine the interfacial properties and element distribution of the CMS/MnGa structure, high-resolution transmission electron microscopy (HRTEM) and energydispersive X-ray spectroscopy (EDX) were used, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation